The Use of Motivation Video “The Gift” & Student Critical Thinking toward Listening Skills of Tenth Grade of SMA Srijaya Negara - Putra, Rian Pratama (Jurnal Ilmiah Dikdaya, 2024)
This study aims to initiate the effectiveness of the use of the motivational video "The Gift" in improving critical thinkingskills and listening skills of tenth grade students at SMA Srijaya Negara. The following is a summary of the study: Criticalthinking skills and listening skills are important competencies that need to be developed in students to support an effectivelearning process. The motivational video "The Gift" was chosen as a learning medium because it is considered capable ofstimulating students' interest and motivation. This study used an experimental method with a pre-test and post-test design.Students were divided into two groups: the experimental group that used the motivational video "The Gift" and the control groupthat used conventional learning methods. The results showed that students who used the motivational video "The Gift"experienced a significant increase in critical thinking skills and listening skills compared to the control group. This increase wasmeasured through tests conducted before and after the intervention. The conclusion is that the use of the motivational video "TheGift" is effective in improving critical thinking skills and listening skills of tenth grade students at SMA Srijaya Negara. Thisvideo can be an alternative to an interesting and effective learning medium to use in class.